Quality of life of psoriatic arthritis patients treated with etanercept - Matusiak, Łukasz; Szepietowski, Jacek (Dermatology Review/Przegląd Dermatologiczny, 2012)
Psoriatic arthritis (PsA) is an inflammatory seronegative spondyloarthropathy. The course of PsA is variable and unpredictable, ranging from mild and non-destructive to a severe, debilitating, erosive arthropathy. Left untreated, patients with PsA can have persistent inflammation, progressive joint damage, severe physical limitations, disability, and increased mortality. Arthritis entails significant impairment of patients’ mental, emotional and functional quality of life (QoL), and additional skin lesions further exacerbate this impairment. If PsA is diagnosed, treatment should be initiated to alleviate signs and symptoms of PsA, inhibit structural damage, and maximize QoL of patients. In recent years, TNF- α inhibitors, including etanercept, have become widely used for the treatment of PsA. This paper summarizes findings on the quality of life in PsA patients treated with etanercept, and shows that such treatment not only controls disease activity but also significantly improves the quality of life.